Numerical calculations and analyses in diagonal type MHD generator - Kien, Le Chi (Vietnam Journal of Science and Technology, 2015)
This paper investigate the influence of the attenuation of magnetic induction on the current distribution etc. in the end regions of the diagonal type nonequilibrium plasma MHD generator by a two-dimensional analysis. The numerical calculations are made for an example of the cesium-seeded helium. As a result, a suitable attenuation of the magnetic induction can make the current distribution very uniform near the end region of generator duct and has little influence on the current distribution in the central part of generator, and the output electrodes can be used without large ballast resistors. Also the internal resistance of the end region and the current concentration at the output electrode edges decrease with the attenuation of magnetic flux density. By the author’s investigation, it is made clear that the output electrodes of the diagonal type nonequilibrium plasma MHD generator should be arranged in the attenuation region of the magnetic induction, since arranging them in the attenuation region of magnetic flux density can become useful for the improvement of the electrical characteristics of generator